The Burden of Musculoskeletal Disease in Sierra Leone. Issue 1 (January 2015) - Elliott, Iain S.; Groen, Reinou S.; Kamara, Thaim B.; Ertl, Allison; Cassidy, Laura D.; Kushner, Adam L.; Gosselin, Richard A.
Abstract: Background: Musculoskeletal disease is a major cause of disability in the global burden of disease, yet data regarding the magnitude of this burden in developing countries are lacking. The Surgeons OverSeas Assessment of Surgical Need (SOSAS) survey was designed to measure the incidence and prevalence of surgically treatable conditions, including musculoskeletal conditions, in patients in low‐ and middle‐income countries, and was administered in the West African nation of Sierra Leone in 2012. Purpose: We attempted to quantify the burden of potentially treatable musculoskeletal conditions in patients in Sierra Leone. Methods: A cross‐sectional two‐stage cluster‐based survey was performed in Sierra Leone using the SOSAS. Two individuals from each randomly selected household underwent a verbal head to toe examination. The musculoskeletal‐related questions from the SOSAS survey in Sierra Leone were analyzed to determine the prevalence of musculoskeletal problems in the study population. Prevalence is reported as the number of respondents with a musculoskeletal problem now and number of respondents with a musculoskeletal problem during the past year. Respondents had "no need" for care, they "received care", or they faced a barrier that prevented them from receiving care. Results: One thousand eight hundred seventy‐five households were targeted, with 1843 undergoing the survey, which yielded 3645 individual respondents. Of the individual respondents, 462 (n = 3645; 12.6% of total; 95% CI, 12%‐13%) had a traumatic musculoskeletal problem during the past year, and 236 (n = 3645; 6% of total; 95% CI, 5%‐7%) respondents had a musculoskeletal problem of nontraumatic etiology. Of respondents with either a traumatic or nontraumatic musculoskeletal problem, 359 (n = 562; 63.9% of total; 95% CI, 59.5‐68.3%) needed care but were unable to receive it with the major barrier reported as financial. Conclusion: Resource allocation decisions in global health are made based on burden of disease data in low‐ and middle‐income countries. The data provided here for Sierra Leone may offer some generalizable insight into the scope of the burden of musculoskeletal disease for low‐ and middle‐income countries, especially in Sub‐Saharan Africa, and provide concrete evidence that musculoskeletal health should be included in the global health discussion. However, there may be important differences across countries in this region, and further study to elucidate these differences seems critical given the large burden of disease and the limited resources available in these regions to manage it.